Resultados da intervenção farmacêutica em um hospital de ensino: O intercâmbio terapêutico como ferramenta de gestão - Suda, Nadia Takako Bernardes [UNIFESP] (2018)
Introduction: Pharmaceutical care in hospitals involves critical management processes, especially by the high costs related to medications. Pharmaceutical Interventions (PI) with the aim of promoting the rational use of medication have been described worldwide. However, there are few reports on therapeutic exchange (TE) as a management tool in Brazilian university hospitals. Objective: Assess whether the PI improves the quality of pharmaceutical care provided to the patient hospitalized and reduces the purchase cost of not standardized medication. Methods: We describe the requests of nonstandardized medications received in two phases of four months each. In the first, we carried out a situational analysis. In the second phase, pharmacists have evaluated the requests whenever the possibility of substitution was given, and then physicians suggested alternatives to them. We analyzed the data from the pharmacy center of Universitary Hospital and applied questionnaires to register the performed PI. Results: Pharmaceutical interventions (PI) with the suggestion of therapeutic exchange (TE) resulted in savings of R$88,764.14. Even with an increase in the number of patients hospitalized in the second period of study, there was a reduction of 4% in the number of requests. More than 60% of these requests were destined to patients with more than 30 (thirty) days of hospitalization. The pediatric units were responsible for 72% and 61.5% of the requests in the first and second study phases, respectively. Pharmacists at the Pharmaceutical Division performed 142 (31.8%) PIs. The rate of acceptance of suggestion by interns was 76%. Of the PIs accepted, 48% were replaced by standardized medications. Although there has been an increase of 3.4% in the waiting time for receiving the medication requested, the answering of requests increased in 16.8% in the PI period. Conclusion: The effects of PI were positive and connected to the objectives proposed in this study.